2008
DOI: 10.1007/s11258-008-9436-8
|View full text |Cite
|
Sign up to set email alerts
|

Germination studies on three critically endangered endemic angiosperm species of the Kashmir Himalaya, India

Abstract: The critically endangered and perennial alpine endemic angiosperms, namely, Aquilegia nivalis, Lagotis cashmeriana and Meconopsis latifolia inhabit such habitats in the Kashmir Himalaya that are characterised by short growing season and heavy snow cover for about 3-4 months during winter season. The seeds of these species under natural conditions experience a long period of pre-chilling during winter prior to their germination in following spring season. Taking cue from such a requirement, present study invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Explants originally cultured on benzyl adenine or kinetin containing medium produced more shoots than those originally cultured on isopentenyladenine containing media. Dar et al [30] also reported seed germination in Meconopsis latifolia, when treated with GA3. Our results are in confirmation with Kuris et al [36] who reported that increased percentage of shoots was achieved in Origanum vulgare L. when cultured on MS medium supplemented with IAA and IBA treatments and showed that the IAA and IBA has higher potential of in vitro root development.…”
Section: Ms Basalmentioning
confidence: 96%
See 1 more Smart Citation
“…Explants originally cultured on benzyl adenine or kinetin containing medium produced more shoots than those originally cultured on isopentenyladenine containing media. Dar et al [30] also reported seed germination in Meconopsis latifolia, when treated with GA3. Our results are in confirmation with Kuris et al [36] who reported that increased percentage of shoots was achieved in Origanum vulgare L. when cultured on MS medium supplemented with IAA and IBA treatments and showed that the IAA and IBA has higher potential of in vitro root development.…”
Section: Ms Basalmentioning
confidence: 96%
“…Treatment of seeds with kinetin (6-furfuryl-aminopurine) had a significant influence on germination percentage in Meconopsis latifolia. Thus, prolonged chilling of seeds followed by their treatment with GA3 under alternate light/dark conditions are the requirements necessary for seed germination in Meconopsis aculeta [30].…”
Section: In Vitro Plantlet Regeneration From Seed Explants Of Meconopmentioning
confidence: 99%
“…Germination and seedling recruitment have also been reported to be very low both in natural habitat and under laboratory conditions (Xie et al, 2002). Several studies conducted for different species of genus Meconopsis revealed the existence of physiological dormancy hindering seed germination (Sulaiman 1993;Dar et al, 2009). …”
Section: Ecologymentioning
confidence: 99%
“…In this process, seeds of M. napaulensis, collected from different populations, were cut into two equal halves in such a way that each part got a portion of the embryo. Then treated with 1% solution of TTC (Dar et al, 2009) and observed under stereo-microscope. Seed viability was revealed by pink TTC precipitation produced by dissected seeds.…”
Section: Pollen and Seed Viabilitymentioning
confidence: 99%
“…Dunn (1997) reported that nutlets of S. germanica have been found unshed for up to 12 months in nature and our results suggest that S. germanica seeds may persist also for long periods of time in the soil. A mechanism that delays germination until the next spring, when conditions become optimal for reproductive success, could be advantageous in harsh habitats (Dar et al, 2009). After seed dispersal, some species, like S. germanica, will experience moist chilling during the colder winter months and subsequently germinate in the next season.…”
Section: Tablementioning
confidence: 99%